2009
DOI: 10.1111/j.1460-9568.2009.06718.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of serotonergic 5‐HT2A/2C receptors: mutual improvement of sleep, cognition and mood?

Abstract: Serotonin [5-hydroxytryptamine (5-HT)] and 5-HT receptors are involved in sleep and in waking functions such as cognition and mood. Animal and human studies support a particular role for the 5-HT(2A) receptor in sleep, which has led to renewed interest in this receptor subtype as a target for the development of novel pharmacological agents to treat insomnia. Focusing primarily on findings in healthy human volunteers, a review of the available data suggests that antagonistic interaction with 5-HT(2A) receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 203 publications
(235 reference statements)
4
53
0
1
Order By: Relevance
“…Ziprasidone's affinity for the reuptake sites is similar to that of the antidepressant imipramine, a drug that produces comparable changes in REM suppression in patients with depression [Gunasekara et al 2002]. The increase in REM latency may have also been mediated by 5-HT 1A agonism as agonists to postsynaptic receptors have been shown to inhibit REM sleep [Landolt and Wehrle, 2009]. Ziprasidone's sleep continuity properties might be related to its antihistaminergic and antidopaminergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ziprasidone's affinity for the reuptake sites is similar to that of the antidepressant imipramine, a drug that produces comparable changes in REM suppression in patients with depression [Gunasekara et al 2002]. The increase in REM latency may have also been mediated by 5-HT 1A agonism as agonists to postsynaptic receptors have been shown to inhibit REM sleep [Landolt and Wehrle, 2009]. Ziprasidone's sleep continuity properties might be related to its antihistaminergic and antidopaminergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…4) TIK-301: It is a melatonergic agonist and serotonergic antagonist drug. It is a more powerful antagonist of serotonergic 5-HT 2c and 5-HT 2b receptors when compared to agomelatine [49]. Theoretically, it has an antidepressant effect.…”
Section: Melatonin Agonist Pharmaceuticalsmentioning
confidence: 99%
“…28,29) Some studies in rats and humans have shown that 5-HT 2A receptor agonists increase wakefulness and inhibit slow-wave sleep (SWS), whereas 5-HT 2A receptor antagonists enhance duration of SWS and EEG low-frequency activity in non-REM sleep. [30][31][32] On the other hand, 5-HT 1A receptors were reported to regulate the activity of the serotonin nervous system, which inhibited the function of 5-HT 2A receptors. 33,34) Kitamura et al 28) demonstrated that 8-OH-DPAT, a potent agonist of 5-HT 1A receptors, inhibited ACTH-induced 5-HT 2A receptor hyperfunction.…”
Section: Discussionmentioning
confidence: 99%